Relationship between knee joint discomfort, self-management behavior, and quality of life in the middle-aged and elderly people in China: A cross-sectional study - Manman Su; Manman Su; Yang Zhou; Yang Zhou; Peipei Zhao; Biyun Zeng; Qidi Zhou (Frontiers Media S.A., 2022)
BackgroundThe aim of this study was to describe the knee joint discomfort, self-management behavior, and quality of life (QoL) in the middle-aged and elderly people in China and to clarify the relationship between the knee joint discomfort, self-management behavior, and QoL.MethodsIt is a cross-sectional study and in this study, a stratified multistage random sampling method was used to collect data on the three factors such as knee joint discomfort, self-management behavior, and QoL among the middle-aged and elderly people in the Hunan Province. Spearman's correlation analysis was used to test the relationship between the knee joint discomfort, self-management behavior, and QoL.ResultsThe results of the present study showed that among them, the prevalence of knee pain was the highest (52.1%), followed by knee weakness (42.5%), numbness (41.8%), cold feeling (40.0%), tenderness (38.3%), and distension feeling (37.5%). Average score of self-management of knee joint discomfort in the middle-aged and elderly people was 2.14 ± 0.67. The level of self-management in each dimension ranged from high to low as emotional management, daily management, symptoms management, and information management. The average scores of physical component summary (PCS) and mental component summary (MCS) were 42.85 ± 5.34 and 43.62 ± 8.43, respectively. The occurrence, frequency, and severity of discomfort symptoms were positively correlated with the symptoms management, daily management, information management, and self-management behaviors, and negatively correlated with the emotional management, PCS and MSC, except for the occurrence of discomfort symptoms (P < 0.05).ConclusionKnee joint discomfort was prevalent in the middle-aged and elderly people. In addition, they displayed a low level of self-management behavior and poor QoL. The middle-aged and elderly people faced knee discomfort symptoms, the more frequent and severe symptoms, the higher level of symptom management, daily management, and information management, and the lower level of emotional management and QoL.